External cephalic version: Predictors of success and influence on caesarean rates. (January 2021) - Correia Costa, Susana; Raposo, Maria Inês; Machado, Ana Paula; Ramalho, Carla; Ayres-de-Campos, Diogo; Montenegro, Nuno
Abstract: Objective: To evaluate the success rate of external cephalic version, predictive factors for success of this maneuver and to examine how it affects mode of delivery, pregnancy and neonatal outcome rates. Study design: Retrospective cross-sectional study performed in a tertiary care university hospital between January 2002 and June 2018. A total of 324 ECVs were performed in 321 pregnancies. Maternal and ultrasound data, procedure-related factors, birth characteristics and neonatal data were collected. Absolute and relative frequencies were used for descriptive analysis and the chi-square test for comparative analysis. Odds ratios with 95 % confidence intervals were calculated. Results: The overall success rate of the procedure was 33, 3%. Multiparity, transverse lie, unengaged breech presentation, low body mass index, soft uterus and palpable fetal head were independent risk factors for success. No statistically significant association was found with other variables. Routine use of ECV allowed a reduction in cesarean delivery rates for breech presentation, with no increase in maternal or neonatal morbidity. Operative delivery rates after successful ECV were similar to those of the general population. Discussion and conclusion: Despite a relatively low overall success rate, routine use of ECV can result in reduced cesarean delivery rates with similar perinatal outcomes. Conveyed information on the success rate of ECV can be adapted to individual patient characteristics.